3D dual-mode OFDM-IM modulation with multi-envelope approach and performance analysis - GUO Yi; HUA Zhuhao; LIU Gang; FU Shaozhong (Tongxin xuebao)
To address the issues of high bit error rate and limited anti-interference capability in current high-dimensional OFDM index modulation systems, a dual-mode orthogonal frequency division multiplexing index modulation scheme based on multi-envelope three-dimensional constellation modulation (3D-DM-OFDM-IM) was proposed. The scheme employed a method of inscribing regular polyhedrons within multiple spherical envelopes to design a 3D constellation diagram. Compared to existing 3D constellation mapping schemes, the minimum Euclidean distance between constellation points has improved. Simulation results show that under the condition of ensuring the same spectral efficiency, the proposed scheme achieves better bit error rate performance and lower peak-to-average power ratio compared to the existing 3D dual-mode OFDM-IM modulation scheme, regardless of low-order modulation or high-order modulation.